Music and belonging between revolution and restoration - Waltham-Smith, Naomi 1983- (Oxford University Press, 2017)
In what ways is music implicated in the politics of belonging? How is the proper at stake in listening? What role does the ear play in forming a sense of community? Music and Belonging argues that music, at the level of style and form, produces certain modes of listening that in turn reveal the conditions of belonging. Specifically, listening shows the intimacy between two senses of belonging: belonging to a community is predicated on the possession of a particular property or capacity. Somewhat counter-intuitively, Waltham-Smith suggests that this relation between belonging-as-membership and belonging-as-ownership manifests itself with particular clarity and rigor at the very heart of the Austro-German canon, in the instrumental music of Haydn, Mozart, and Beethoven. Music and Belonging provocatively brings recent European philosophy into contact with the renewed music-theoretical interest in Formenlehre, presenting close analyses to show how we might return to this much-discussed repertoire to mine it for fresh insights. The book's theoretical landscape offers a radical update to Adornian-inspired scholarship, working through debates over relationality, community, and friendship between Derrida, Nancy, Agamben, Badiou, and Malabou. Borrowing the deconstructive strategies of closely reading canonical texts to the point of their unraveling, the book teases out a new politics of listening from processes of repetition and liquidation, from harmonic suppressions and even from trills. What emerges is the enduring political significance of listening to this music in an era of heightened social exclusion under neoliberalism
Includes bibliographical references and index
Keywords: Mozart, Wolfgang Amadeus -- 1756-1791; Beethoven, Ludwig van -- 1770-1827; Haydn, Joseph -- 1732-1809; Geschichte 1700-1800; Geschichte 1800-1900; Geschichte; Musik; Gemeinschaft; Klassik; Europa; Haydn, Joseph 1732-1809 / Criticism and interpretation; Mozart, Wolfgang Amadeus 1756-1791 / Criticism and interpretation; Beethoven, Ludwig van 1770-1827 / Criticism and interpretation; Music / History and criticism / 18th century; Music / Analysis, appreciation / 18th century; Music / History and criticism / 19th century; Music / Analysis, appreciation / 19th century; Belonging (Social psychology) / History / Europe